Protective and Therapeutic Effect of Oleoresin of Pistacia atlantica in Acetic Acid-induced Colitis in Rat - S Farokhi; GhR Bahrami; A Babaie; MH Farzaei (Institue of Medicinal Plants, ACECR, 2019)
Background: Ulcerative colitis is an idiopathic chronic, relapsing inflammation of the colon which is resulted from dysregulation of the mucosal immune system. In Iranian traditional medicine, oleoresin from Pistacia atlantica is used to treat gastrointestinal disorders, including peptic ulcers, dyspepsia and intestinal inflammation. Objective: In this study, we examined the therapeutic and protective effects of oleoresin in acetic acid-induced colitis in rat. Methods: The oleoresin was dissolved in Tween 80% (1% v / v) and doses of 100, 200 and 400 mg/kg were administered orally to animals. Three days after colitis induction, the rats were treated for 6 days and after determining the most effective dose in the treatment, the protective effect was evaluated using the optimal dose of the oleoresin for 6 days. In day 6, colitis was induced and continued for 3 days. At the end, animals were sacrificed for microscopic and macroscopic examination of colon tissues. Results: Dose dependently, Oleoresin of P. atlantica showed therapeutic effects on microscopic and macroscopic examination of colon tissue of rats with ulcerative colitis  induced by acetic acid, in comparison with control group(P<0.05). However, there was no significant difference between treatment groups and the control in the protective method (P>0.05). Conclusion: This study showed the beneficial effects of anti-inflammatory and wound healing oleoresin of P. atlantica in acetic acid- induced ulcerative colitis in rats.